"Your one wild and precious life" Women on the Road of Ministry - Johnson, Elizabeth A. 1941- (2019)
While women continue to engage in ministry in increasing numbers, their presence and activity is an unresolved issue in terms of ecclesial structure and meaning. In the past the effects of the Second Vatican Council and the twentieth-century women's movement combined to open the door to women's active engagement. The ongoing foundation of women's vocation to ministry lies, in the present as always, in the significance of baptism; its theology and ritual are the same for women as for men. In the face of current impasse, the dangerous memory of biblical women in ministry at the origins of the church offers inspiration and hope for the future.
Keywords: Gaudium et Spes; Holy Spirit; Inter Insignores; Lumen Gentium; Mary Magdalen; Baptism; IMAGE OF CHRIST; Patriarchy; women disciples of Jesus; Women in Rome; women in ministry